2013
DOI: 10.11634/216796221302332
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Male Involvement in Family Planning and Reproductive Health in Bangladesh

Abstract: This study examined the factors that influence male participation in family planning and reproductive health in Bangladesh. Male involvement in family planning and reproductive health was measured by a simple composite index. This study revealed that male involvement in family planning is high about 63.2 percent in this area. Chisquared tests and binary logistic regression analysis were applied to determine the relationship between various kinds of variables and the probability of male involvement in family pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 5 publications
10
36
1
Order By: Relevance
“…15 Educated men have proper knowledge on modern contraceptive. 15,23 This study reveals that men have considerable knowledge on modern contraceptives, including female methods. Fear of side-effects is one of the reasons for not using modern contraceptive and thus lead them to use traditional methods.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…15 Educated men have proper knowledge on modern contraceptive. 15,23 This study reveals that men have considerable knowledge on modern contraceptives, including female methods. Fear of side-effects is one of the reasons for not using modern contraceptive and thus lead them to use traditional methods.…”
Section: Discussionmentioning
confidence: 90%
“…Appropriate policies should be developed by considering the related factors to increase males' contraceptive knowledge and hence increase male participation in family planning and reproductive health in Bangladesh. 15,18,23 There were some limitations of the study. The researcher compiled the complete list of the all married men age (15-49 years) from those selected wards.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also found an association between women's educational level and male involvement in FP and other related issues. 5,14,18 Birth spacing was also discovered to be significantly associated with male involvement in FP. Men whose partner's interval between the last two deliveries was 13 months and more demonstrated higher levels of involvement in FP.…”
Section: Factors Associated With Male Involvementmentioning
confidence: 94%
“…This result compares with those of other studies conducted in Nigeria, Bangladesh, Papua New Guinea and Nepal where men who were uneducated or had primary level of education were likely to have a more conservative perception towards FP. 3,5,[15][16][17][18] Educated men are more likely to have good knowledge of FP which can enable them to make informed decisions on the benefits and risks of FP methods. Uneducated men, on the other hand, often have misconceptions about FP methods, especially with regards to side effects.…”
Section: Factors Associated With Male Involvementmentioning
confidence: 99%
See 1 more Smart Citation